Development and Research Directions in Seafarers’ Welfare and Rights: A Bibliometric Analysis Between 1920 and 2023 - Hanh-Thi Hong Hoang; Le-Thanh Nguyen; Sung-Ho Park; Jong-Kwan Kim (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
Seafarers make a critical contribution to civil society; however, they are exposed to various occupational health hazards on board ships and have historically not been granted fundamental rights. For over one century, since the first international instrument – the National Seamen’s Code Recommendation – was adopted in 1920, global seafarers have been fighting for their rights and welfare. The International Labour Organization adopted the Maritime Labour Convention as a “Bill of Rights” for seafarers in 2006, and then this instrument entered into force in 2013. After more than 10 years of implementation, it is necessary to thoroughly review the process and achievements that the maritime industry has been performing to protect seafarers’ rights and ensure their welfare. This study employed bibliometric and content analysis methods to offer a comprehensive and succinct description of the progress in academic research on seafarers’ welfare and rights from 1920 to 2023 in the Scopus database. It identified the topics, envisaged the current challenges of seafarers, and suggested imperative measures and research directions in the future. To enhance the rights and welfare of seafarers, leading suggestions from this study include (i) regulatory improvements and effective enforcement of the Maritime Labour Convention 2006, (ii) improving occupational health and safety; mental health and wellbeing of seafarers, (iii) training their knowledge and skills to cope with challenges, and (iv) developing women seafarers’ prospects.